Incidence of Malignancy Related Pericardial Effusion in a Tertiary Hospital - Fatema, Nilufar; Rahman, Wahidur; Samdani, Tasrina Shamnaz; Rahman, M Asadur; Rahman, Afsana; Siddiqua, Ayesha; Aziz, Ahmed Monjurul; Sultan, Md Ashraf Uddin; Sharmin, Farzana; Arzu, Jahanara (University Heart Journal, 2017)
Back ground: Malignancy related pericardial effusion (PE) may represent a terminal event in patients with therapeutically unresponsive disease. Pericardial tamponade (PT) is a co morbid condition in many diagnosed malignant cases. Selection of patients with malignancies who are responsive to available treatment may achieve significant improvement in palliation. Early detection of pericardial tamponade and appropriate intervention (Pericardiocentesis) or Subxyphoid pericardiotomy may result long term survival benefit. Objective: Early detection and management of PE and tamponade in malignant cases. Methods: Color Doppler (C-D) echocardiography was done in 260 patients with underlying malignancies on chemo or radiotherapy from oncology department of Delta Medical college and hospital from May 2016 to December 2016. These cases were reviewed retrospectively for clinical features, diagnosis and therapy for their malignancy. Results: 81% have shortness of breath, sign of pulsus paradoxus and pericardial tamponade were found in 22% and 5% patients respectively. During echocardiography, pericardial effusion was found in 102 patients. 65% have mild pericardial effusion, whereas 27% have moderate and 8% have severe PE. Effusions with malignancy comprising of 40% adenocarcinomas of lung, 15% carcinoma (Ca) of pharynx, 10% Ca breast, 10% lymphoma, 10% is Carcinoma of unknown primary, 8% Ca esophagus and 7% others (Renal, Hepatic, ovary & cheek). University Heart Journal Vol. 12, No. 1, January 2016; 23-25